2018
DOI: 10.1038/s41598-018-29086-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive map of age-associated splicing changes across human tissues and their contributions to age-associated diseases

Abstract: Alternative splicing contributes to phenotypic diversity at multiple biological scales, and its dysregulation is implicated in both ageing and age-associated diseases in human. Cross-tissue variability in splicing further complicates its links to age-associated phenotypes and elucidating these links requires a comprehensive map of age-associated splicing changes across multiple tissues. Here, we generate such a map by analyzing ~8500 RNA-seq samples across 48 tissues in 544 individuals. Employing a stringent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 51 publications
3
64
1
Order By: Relevance
“…In parallel, transcripts from SINEs/Alus, a family of repetitive elements particularly abundant in euchromatin, have been reported to accumulate in senescent cells with an impact on genome integrity (12). Finally, several studies have reported that cellular senescence is associated with numerous changes in the outcome of alternative pre-mRNA splicing (13). This results in the production of senescent toxins including progerin, a variant of Lamin A associated with the Hutchinson-Gilford progeria syndrome (14), while also favoring the synthesis of S-Endoglin and p53beta that may have a similar prosenescence activity (15) (16).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, transcripts from SINEs/Alus, a family of repetitive elements particularly abundant in euchromatin, have been reported to accumulate in senescent cells with an impact on genome integrity (12). Finally, several studies have reported that cellular senescence is associated with numerous changes in the outcome of alternative pre-mRNA splicing (13). This results in the production of senescent toxins including progerin, a variant of Lamin A associated with the Hutchinson-Gilford progeria syndrome (14), while also favoring the synthesis of S-Endoglin and p53beta that may have a similar prosenescence activity (15) (16).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome change is a significant molecular signature of aging and serves as an essential factor in the aging-associated functional decline across organs ( Benayoun et al, 2019 ; Braun et al, 2016 ; Schaum et al, 2019 ; Stoeger et al, 2019 ; Yu et al, 2014 ; Zahn et al, 2007 ). Several earlier studies have profiled and analyzed age-correlated gene expression in different organs in rodents ( Barns et al, 2014 ; Benayoun et al, 2019 ; Braun et al, 2016 ; de Magalhães et al, 2009 ; Ori et al, 2015 ; Schaum et al, 2019 ; Stoeger et al, 2019 ; Yu et al, 2014 ; Zahn et al, 2007 ; Zhuang et al, 2019 ) and humans ( Ahadi et al, 2020 ; Glass et al, 2013 ; Wang et al, 2018 ; Yang et al, 2015 ; Zhuang et al, 2019 ). The majority of the genes altered during aging are associated with inflammatory responses ( Benayoun et al, 2019 ; Schaum et al, 2019 ; Stegeman and Weake, 2017 ), highlighting chronic inflammation as a hallmark of aging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tumour-specific splice variants of genes that control cell proliferation and apoptosis have been reported in the last decade 23–29 32 33. These processes are influenced both by genetic factors and environmental factors, for example, immune responses,34 35 age,36 heat stress37 and DNA damage 38. CNAs have also been described as having a particular association with AS 16 19.…”
Section: Discussionmentioning
confidence: 99%